Pilot Study to Examine the Use of Self-Generation to Improve Learning and Memory in People With Traumatic Brain Injury - Goverover, Yael; Chiaravalloti, Nancy; DeLuca, John (The American journal of occupational therapy, 2010)
People with traumatic brain injury (TBI) experience memory and learning difficulties. Difficulty in the initial acquisition of information is a primary reason people with TBI experience difficulties in learning and memory. Treatment focusing on improving the acquisition of information will likely improve both recall and recognition performance. In the “generation effect,” items self-generated are remembered better than items read or otherwise provided. The purpose of this study was to examine the application of the generation effect in improving memory for functional activities. The study used a within-subjects design and included 10 participants with TBI and 15 healthy control participants. Results demonstrated that material learned under the generated learning conditions was recalled better than when generated under provided learning conditions. This finding was true in both the TBI and the control groups. These results provide initial evidence supporting the use of self-generation to improve new learning of functional tasks for people with TBI.